2003
DOI: 10.1021/es0209464
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Polystyrene Plastic under Fluorescent Light

Abstract: Plastic is used widely all over the world, due to the fact that it is low cost, is easily processable, and has lightweight properties. However, the hazard of discarding waste plastic, so-called "white pollution", is becoming more and more severe. In this paper, solid-phase photocatalytic degradation of polystyrene (PS) plastic, one of the most common commercial plastics, over copper phthalocyanine (CuPc) sensitized TiO2 photocatalyst (TiO2/CuPc) has been investigated under fluorescent light irradiation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(121 citation statements)
references
References 31 publications
1
118
0
2
Order By: Relevance
“…It showed that little phenol was decomposed with pure TiO 2 under visible light, while with PFB/TiO 2 nearly 75% of the phenol was removed. It is suggested that PFB is an effective photosensitizer, as has been reported for some dyes [9][10][11]. Kinetically, the degradation reaction showed the firs-order behavior.…”
Section: Photocatalytic Removal Of Phenolsupporting
confidence: 54%
See 3 more Smart Citations
“…It showed that little phenol was decomposed with pure TiO 2 under visible light, while with PFB/TiO 2 nearly 75% of the phenol was removed. It is suggested that PFB is an effective photosensitizer, as has been reported for some dyes [9][10][11]. Kinetically, the degradation reaction showed the firs-order behavior.…”
Section: Photocatalytic Removal Of Phenolsupporting
confidence: 54%
“…This indicated that interactions between TiO 2 and PFB were responsible for the photocatalytic degradation, because neither TiO 2 nor PFB alone is effective. It is generally believed [10,11] that upon visible light irradiation, the photosensitizer adsorbed onto the surface of TiO 2 gets excited and injects an electron into the conduction band of TiO 2 . This conduction band electron is subsequently captured by dioxygen adsorbed onto the surface of TiO 2 and induces the generation of ·O 2 -/HO· radicals which attack organic pollutants to yield the ultimate products.…”
Section: Photocatalytic Removal Of Phenolmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it seems that the composition of plastic with TiO 2 nanoparticles is a useful means to decompose solid polymer in the open air. Researchers have recently studied the solid-phase photocatalytic degradation of polymer-TiO 2 nano-composite [8][9][10][11][12] . But the photodegradation properties of PP nano-composites has rarely been studied.…”
Section: Hoomentioning
confidence: 99%